Confiscation of property corruption convicts refund and their families for the loss - J.S Panjaitan, Marojahan (Opción, 2019)
This research tries to find out how to determine and how to restore the state losses, as well as additional punishment forms that need to be given to the convicted corruption. In accordance with the purpose of this study, the nature of the research is analytical descriptive research. As a result, all losses, whether in the form of money taken, or losses in the state economy, must be calculated and paid in cash. In conclusion, Additional criminal sanctions in the form of the repeal of political rights and social sanctions need to be given to the convicted corruption.